Fuzzy logic control in energy systems : with design applications in MATLAB /Simulink - Altas, Ísmail H. (IET energy engineering series ;, 2017)
This book is about fuzzy logic control and its applications in managing, controlling and operating electrical energy systems. It provides a comprehensive overview of fuzzy logic concepts and techniques required for designing fuzzy logic controllers, and then discusses several applications to control and management in energy systems.